THE TRANSFORMATION OF TALENT MANAGEMENT IN THE FACE OF THE ARTIFICIAL INTELLIGENCE ERA IN TECHNOLOGY COMPANIES IN INDONESIA - Khaeruman Khaeruman; Irma Nurmala Dewi; Anita Ariffin (Yayasan Education and Social Center, 2026)
The transformation of talent management has become a strategic issue for technology companies in line with the rapid development of artificial intelligence (AI). This study aims to analyze the transformation of talent management in the face of the AI era within technology companies in Indonesia. The research employs a qualitative approach using a case study design. Data collection was carried out through in-depth interviews, observation, and documentation at PT Tekno Maju Indonesia during November–December 2025. Data analysis utilized manual coding and thematic analysis, encompassing data reduction, data presentation, and the drawing of conclusions. The findings indicate that the implementation of AI has improved the efficiency of the recruitment process through the automation of candidate screening; however, final decisions still require an assessment by Human Resources regarding cultural fit and soft skills. Furthermore, the company has revised its talent development strategy by prioritizing AI literacy, critical thinking skills, adaptability, and continuous upskilling programs. The study also identified the phenomenon of ‘AI anxiety’, which affects employees’ readiness to face digital transformation. To address this, companies are implementing transparent communication, continuous training, and a human-centered approach to change management. This research contributes to the body of knowledge on AI-driven talent management transformation. It serves as a reference for technology companies in designing adaptive, innovative, and sustainable human resource management strategies in the era of artificial intelligence.